The Effect of Listening to Holy Quran Recital on Pain and Length of Stay Post-CABG: A Randomized Control Trial - Mohannad Eid Aburuz; Ghadeer Al-Dweik; Fatma Refaat Ahmed (Critical Care Research and Practice)
Background. Nearly, 75% of patients post-CABG complain of moderate to severe pain during their hospital stay. Nonpharmacological interventions have been investigated; however, the effect of Holy Quran recital post-CABG is still not well studied, especially in developing Islamic countries. Objective. To investigate the effect of listening to the Holy Quran recital on pain and length of stay post-CABG. Methods. This was a randomized control trial on 132 patients recruited from four hospitals in Amman, Jordan. The intervention group listened to the Holy Quran recited for 10 minutes twice daily while the control group received the usual care. Data were analyzed using paired and independent samples t-tests. Results. Paired t-test testing showed that there was a significant reduction in the pain level, (M [SD], 6.82 [2.27] vs. 4.65 [2.18], t = 23.65, p < 0.001) for the intervention group. In addition, the intervention group had shorter LoS in the ICU and in the hospital compared to the control group, (M [SD], 5.0 [4.02] vs. 6.58 [4.18], t = −2.1, p < 0.05), (M [SD], 10.15 [9.21] vs. 15.01 [13.14], t = −2.6, p < 0.05), respectively. Conclusions. Listening to the Quran was significantly effective in improving pain intensity among post-CABG patients and shortening their hospital/ICU stay. This trial is registered with NCT05419554.